Determining Consensus in Distributed Computer Decision Support System - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The problem of using consensus methods in solving knowledge conflict in distributed decision support system is presented in this article. The manner of decision representation behind assistance of multiattrib and multivalue structure, profile of decisions and the problem of knowledge conflicts are characterized. Next, the heuristics algorithm determining consensus for profile consisting of a set of decision structures was elaborated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 217-224
Keywords: systemy wspomagania decyzji; systemy rozproszone; decision support systems (dss); systems diffuse